Dinâmica populacional de Andiroba (Carapa Guianensis Aublet) em Roraima, extremo norte da Amazônia - Marques, Izabelle Luiza Lopes (2012)
The harvest of non-timber forest products is a way of boosting income for poor people in the tropics, and encouraging forest conservation. However, harvesting of such products may changes ecological processes of the exploited species at different levels. These changes could affect vital rates of individuals and demographic and genetic parameters of the populations. To ensure that the harvesting is a sustainable activity and generate socio-economic development for the people of the forest, it is essential to add to traditional knowledge information about the ecology of the species and appropriate management techniques. The Andiroba (Carapa guianesis Aublet.) is a multipurpose tree, providing one of the most widely used medicinal oils in the Amazon, and high-quality wood. Despite market’s growing interest, information on the species’ biology, economic, and ecological aspects of the seed harvesting and oil processing remain limited. This study aimed to evaluate seed production and population dynamics of C. guianesis in a natural stand in southern Roraima. In a nine-hectare plot, all individuals of C. guianensis with DBH ≥ 10 cm were classified into developmental stages and tree individual seed production was estimated during a period of six years. Individuals with DBH <10 cm, named recruits, were monitored in 27 subplots of 25 x 25 m (1.7 ha). Matrix models were used to (i) evaluate population structure, (ii) estimate finite rate of increase (λ) and (iii) identify priority demographic parameter for population persistence. We used simulations to test different kinds of harvesting intensity to suggest management recommendations. Tree diameter can be used to identify productive individuals; trees with a diameter above 35 cm are the most productive. According to our simulations, the studied population is stable and, if current conditions remain unchanged, there is no risk of population decline. The main population parameter for the maintenance of C. guianensis population was the survival of adult II (DBH≥ 35 cm). Simulations of harvesting intensity, regeneration increase, or withdrawal of adults I (10 <DBH <35 cm), did not affect the rate of population growth. However, removal of only two adult II (or less than a 3% interference in the survival of individuals with higher reproductive potential of the population) results in a decrease of population growth rate (λ <1). Thus, maintaining current conditions, the growth rate of the population studied is consistent with seeds harvesting. Multiple uses of this species (wood and seeds) should avoid cutting trees in the most productive classes (DBH ≥ 35 cm) to avoid compromising population growth.